PENGARUH BEBAN KERJA, MOTIVASI KERJA, DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI BIDANG PEMANFAATAN PUSDATIN KEMENDIKBUD SELAMA WORK FROM HOME - Nadyasyifa Annisa Syakur (2021)
This research is a quantitative research, the purpose of this research is to know the influence of Workload, Motivation and Work Discipline on Employee Performance in the field of Utilization pusdatin Kemendikbud during Work From Home. The population in this study is all employees in the field of Utilization Pusdatin Kemendikbud which amounts to 65 employees. This study used a sample of 65 employees using saturated sample techniques. This study uses primary data conducted by disseminating questionnaires / questionnaires. Data analysis techniques used in this study is a data analysis technique that uses statistical methods in the form of Partial Least Square (PLS). test results obtained in this study (1) Workload positively and significantly affect the Performance of Employees in the field of Utilization Pusdatin Kemendikbud during Work From Home, (2) Motivation positively and significantly affect the Performance of Employees in the field of Utilization Pusdatin.